1986
DOI: 10.1111/j.1600-0897.1986.tb00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenic Disturbance Induced in Mice by Combined Local Injection of Monoclonal Antibodies to Sertoli Cell and to Basal Lamina of Seminiferous Tubule

Abstract: Two kinds of hybridoma clones, one producing monoclonal antibodies against Sertoli cell (TM-1) and the other the basal lamina of the seminiferous tubule (TM-2), were raised by fusion between P3X63Ag8-653 mouse myeloma cells and spleen cells of BALB/c mice (H-2d) immunized with testicular homogenate of the same inbred mice. Immunohistochemically, TM-1 reacted specifically with cytoplasmic component of Sertoli cell and TM-2 with basal lamina of the seminiferous tubule. Using these monoclonal antibodies, spermato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this model, autoimmune reactions are evoked against the haploid cells which possess autoimmunogenic antigens, as well as against spermatogonia, Sertoli cells, Leydig cells, and the basement membrane of the seminiferous tubule which do not intrinsically possess immunogenic antigens [37,40,41]. In other experimental models, EAO was induced by double immunization with testicular antigens without the use of any adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, autoimmune reactions are evoked against the haploid cells which possess autoimmunogenic antigens, as well as against spermatogonia, Sertoli cells, Leydig cells, and the basement membrane of the seminiferous tubule which do not intrinsically possess immunogenic antigens [37,40,41]. In other experimental models, EAO was induced by double immunization with testicular antigens without the use of any adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the employment of CFA and BP has proven to be valuable for indirect alteration of the BTB [ 17 , 18 ]. Further, immunization with TH in combination with CFA and BP induced an autoimmune reaction against germ cells within the BTB (= autoimmunity against haploid cells) and also against testicular components outside the BTB (= autoimmunity against spermatogonia, Sertoli cells, Leydig cells and the basement membrane of the seminiferous tubule) [ 5 , 29 , 30 , 31 ]. We also revealed that autoantibodies were detected only against haploid cell antigens in testicular germ cell-induced EAO sera [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using lymphocytes of donor mice that received the similar immunization schedule, Mahi-Brown et al (1987) demonstrated a successful transfer of EAO to naive recipient mice by performing a challenge of the donor lymphocytes with testis antigens in vitro before the cell transfer. It is possible that immunization with a whole testis homogenate elicits not only immune responses against the germ cells, but also the responses against other testicular components such as Leydig cells, Sertoli cells, and basal lamina of the seminiferous tubules (Sato et al, 1981;Ichinohasama et al, 1986). Effector cells for adoptive transfer of EAO of our model were CD4+ T cells.…”
Section: Discussionmentioning
confidence: 94%
“…Firstly Bernard et al (1978) succeeded in adoptive trans-fer of murine EAO using donor mice immunized with testis homogenate + CFA + BPV. It is possible that immunization with a whole testis homogenate elicits not only immune responses against the germ cells, but also the responses against other testicular components such as Leydig cells, Sertoli cells, and basal lamina of the seminiferous tubules (Sato et al, 1981;Ichinohasama et al, 1986). The recipients were athymic nude mice which were injected with BPV.…”
Section: Discussionmentioning
confidence: 99%